Context-free tree grammars are as powerful as context-free jungle grammars - Drewes, Frank; Engelfriet, Joost (Acta Cybernetica, 2015)
Jungles generalize trees by sharing subtrees and allowing garbage. It is shown that IO context-free tree grammars generate the same jungle languages as context-free jungle grammars. Also, they define the same subsets of any algebra.